The effectiveness of exposure to ultraviolet radiation on biological objects - Korablev Ruslan; Belokurov Vladimir; Busarin Eduard; Likhachev Dmitry; Golev A. (BIO Web of Conferences, 2024)
The article discusses the pre-sowing treatment of seeds of scots pine (Pinus sylvestris L.) with ultraviolet (UV) irradiation in order to increase their germination and germination energy. Seed treatment was carried out under the influence of a halogen incandescent lamp of the KGM 12-100 type, from the radiation spectrum of which ultraviolet rays with a wavelength of 365 nm were isolated. The work used radiation doses that corresponded to exposures from 1 to 20 minutes. After that, the germination and germination energy of seeds were studied; the safety and growth dynamics of seedlings in laboratory and field conditions; the mechanism of UV radiation exposure at the cellular and subcellular level was considered. The studies were carried out using the circular dichroism method. The specificity of changes in enzymatic systems under the influence of stress factors has been revealed.